Loyang Mendale Situs Hunian Prasejarah di Pedalaman Aceh: Asumsi Awal Terhadap Hasil Penelitian Gua-gua di Kabupaten Aceh Tengah, Provinsi Nanggroe Aceh Darussalam - Taufiqurrahman Setiawan (Berkala Arkeologi Sangkhakala, 2009)
AbstractIn Central of Aceh, there were an indications of the use of cave and rock shelter as a prehistoric settlement site. Indications of prehistoric settlement site was found among others in Loyang Mendali, Loyang Koro, Loyang Datu and also in Putri Pukes. To prove that indication, further research has been done with the excavation of the cave and rock shelter. Therefore, Balai Arkeologi Medan did the excavation in one of the cave, Loyang Mendali and obtained some data that provided an initial description on prehistoric settelment in Central Aceh.